The Role of The Tourism Sector in Post Pandemi Covid-19 Economic Growth - Heru Widodo; Machin Machin; Ahmad Sukendi; Hevy Susanti (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2022)
The purposes of this study are 1. To find out the Condition of the Tourism Sector in Lamongan Regency After the Covid-19 Pandemic, 2. To find out the Role of the Tourism Sector in Lamongan Regency's Economic Growth After the Covid-19 Pandemic. the research that will be used is analytical research with a qualitative approach. This research was conducted in Lamongan Regency. With an allocation of 3 months starting in mid-March, April, May 2022. Data collection techniques are through observation, documentation and interviews (Interview). In this study, the analytical method used is descriptive method with a qualitative approach. The results of the study are as follows: 1. The condition of the Tourism Sector in Lamongan Regency After the Covid-19 Pandemic has experienced an increase in the number of visitors and financial income from entrance tickets, parking and hotels/inns, restaurants/eateries and shopping for souvenirs typical of Lamongan. The Role of the Tourism Sector in the Economic Growth of Lamongan Regency After the Covid-19 Pandemic is by providing contributions to PAD